The impact of board independence, gender diversity and nationality diversity on firm performance / Aftab Mohd Idris and Ousama A. A. - Mohd Idris, Aftab; A. A, Ousama (Universiti Teknologi MARA, 2021)
This study aimed to examine the relationship between board structure and firm performance measured by return on equity (ROE) and return on asset (ROA). 42 firms listed on the Qatar Stock Exchange (QSE) in 2018 were examined, using regression analysis. The study found that gender diversity (i.e., female directors on the board) had a positive significant relationship with firm performance in both measures, i.e., ROE and ROA. In addition, only board meeting and non-executive directors had significant relationships with firm performance measured by ROA. The findings of the study have some practical implications for some stakeholders, such as listed companies in Qatar and the Qatar Financial Market Authority. The Qatari listed companies will be able to understand the impact of board structure and the complementary benefits that may affect firm performance and thus strengthen the function of their boards. The Qatar Financial Market Authority will be able to understand the current practices of the corporate governance (CG) code; its strengths and weakness. Hence, it will be able to improve the code in order to overcome the weaknesses and strengthen good practices.